Evolution and Stress Responses of CLO Genes and Potential Function of the GhCLO06 Gene in Salt Resistance of Cotton - Fu, Xiaokang; Yang, Yonglin; Kang, Meng; Wei, Hengling; Lian, Boying; Wang, Baoquan; Ma, Liang; Hao, Pengbo; Lu, Jianhua; Yu, Shuxun; Wang, Hantao (Frontiers in Plant Science, 2022)
The caleosin (CLO) protein family displays calcium-binding properties and plays an important role in the abiotic stress response. Here, a total of 107 CLO genes were identified in 15 plant species, while no CLO genes were detected in two green algal species. Evolutionary analysis revealed that the CLO gene family may have evolved mainly in terrestrial plants and that biological functional differentiation between species and functional expansion within species have occurred. Of these, 56 CLO genes were identified in four cotton species. Collinearity analysis showed that CLO gene family expansion mainly occurred through segmental duplication and whole-genome duplication in cotton. Sequence alignment and phylogenetic analysis showed that the CLO proteins of the four cotton species were mainly divided into two types: H-caleosins (class I) and L-caleosins (class II). Cis-acting element analysis and qRT–PCR suggested that GhCLOs might be regulated by abscisic acid (ABA) and methyl jasmonate (MeJA). Moreover, transcriptome data and qRT–PCR results revealed that GhCLO genes responded to salt and drought stresses. Under salt stress, gene-silenced plants (TRV: GhCLO06) showed obvious yellowing and wilting, higher malondialdehyde (MDA) content accumulation, and significantly lower activities of superoxide dismutase (SOD) and peroxidase (POD), indicating that GhCLO06 plays a positive regulatory role in cotton salt tolerance. In gene-silenced plants (TRV: GhCLO06), ABA-related genes (GhABF2, GhABI5 and GhNAC4) were significantly upregulated after salt stress, suggesting that the regulation of salt tolerance may be related to the ABA signaling pathway. This research provides an important reference for further understanding and analyzing the molecular regulatory mechanism of CLOs for salt tolerance.